Oral Pathobiont-Induced Changes in Gut Microbiota Aggravate the Pathology of Nonalcoholic Fatty Liver Disease in Mice - Yamazaki, Kyoko; Kato, Tamotsu; Tsuboi, Yuuri; Miyauchi, Eiji; Suda, Wataru; Sato, Keisuke; Nakajima, Mayuka; Yokoji-Takeuchi, Mai; Yamada-Hara, Miki; Tsuzuno, Takahiro; Matsugishi, Aoi; Takahashi, Naoki; et al. (Frontiers in Immunology, 2021)
BACKGROUND & AIMS: Periodontitis increases the risk of nonalcoholic fatty liver disease (NAFLD); however, the underlying mechanisms are unclear. Here, we show that gut dysbiosis induced by orally administered Porphyromonas gingivalis, a representative periodontopathic bacterium, is implicated in the deterioration of NAFLD pathology. METHODS: C57BL/6N mice were administered the vehicle, P. gingivalis, or Prevotella intermedia, another periodontopathic bacterium with weaker periodontal pathogenicity than P. gingivalis, followed by feeding on a choline-deficient, l-amino acid-defined, high-fat diet with 60 kcal% fat and 0.1% methionine (CDAHFD60). The gut microbial communities were analyzed by pyrosequencing the 16S ribosomal RNA genes. Metagenomic analysis was used to determine the relative abundance of the KEGG pathways encoded in the gut microbiota. Serum metabolites were analyzed using nuclear magnetic resonance-based metabolomics coupled with multivariate statistical analyses. Hepatic gene expression profile was analyzed by DNA microarray and subsequent quantitative polymerase chain reaction analyses. RESULTS: CDAHFD60 feeding induced hepatic steatosis, and together with bacterial administration, it further aggravated the NAFLD pathology with increased fibrosis. Gene expression analysis of liver samples revealed that genes involved in the NAFLD pathology were perturbed, and the two bacterium induced distinct expression profiles. This might be due to quantitative and qualitative differences in the influx of bacterial products in the gut because the serum endotoxin level, composition of the gut microbiota, and serum metabolite profiles induced by the ingested P. intermedia and P. gingivalis were different. CONCLUSIONS: Swallowed periodontopathic bacteria aggravate the NAFLD pathology, likely due to dysregulation of gene expression by inducing gut dysbiosis and subsequent influx of gut bacteria and/or bacterial products.